Jubaji, a Neo-Elamite (Phase IIIB, 585–539 BC) Tomb in Ramhurmuz, Khuzestan. Issue 2 (3rd July 2019) - Ahmadinia, Roonak; Shishegar, Arman
ABSTRACT: In May 2007, a Neo-Elamite period (phase IIIB) burial site was discovered during excavations carried out as part of a piping project by the Khuzestan Water and Sewage Company around Jubaji village, which is near the town of Ramhurmuz, Khuzestan province. The site included a small tomb structure and two bronze coffins. A large number of diverse funerary objects were recovered both inside and outside the coffins, having been scattered as a result of the action of mechanical machinery. Several inscriptions were preserved on gold items, one of which includes the royal name Shutur-Nahunte son of Indada. This paper aims to introduce and describe the tomb and its related artefacts and outline some historical interpretations. A hypothetical reconstruction of the site and the much damaged coffins is also given at the end.